Photophysical properties and photoelectrochemical performances of sol-gel derived copper stannate (CuSnO3) amorphous semiconductor for solar water splitting application - Kim, Bit Na; Seo, Gab Kyung; Hwang, Sung Won; Yu, Hakki; Ahn, Byungmin; Seo, Hyungtak; Cho, In Sun (Ceramics International, 2018)
Copper tin oxide, CuSnO3 (CSO), is an amorphous oxide semiconductor with a band-gap of 2.0–2.5 eV, and it is an attractive material for diverse applications such as transparent conducting oxides, transistors, and optoelectronic devices. In this study, we fabricated CSO thin films on fluorine-doped tin oxide (FTO)/glass substrates using a facile sol-gel process, and their optical properties, band structure and photoelectrochemical (PEC) properties were investigated using UV–Vis spectroscopy, photocurrent-density-potential (J-V) curves, electrochemical impedance spectroscopy, and Mott-Schottky analysis. The CSO film synthesized at 500 °C had an amorphous phase and a band gap of ~ 2.3 eV with n-type behavior, while the films synthesized at 550 °C and 600 °C had a phase mixture (SnO2 + CuO). We identified for the first time that the CSO film could be applied to photoelectrodes for photoelectrochemical water-splitting systems. Importantly, when combining the CSO with nanostructured WO3 film, i.e., the bilayer heterojunction of the a-CSO/WO3 showed enhanced PEC performances (cathodic shift of onset potential, increase of photocurrent generation and O2 evolution) compared to the pristine WO3 film.
Keywords: Amorphous oxide semiconductor (AOS); CuSnO3; Fluorine doped tin oxide; Mott-Schottky analysis; Photocurrent generations; Photoelectrochemical performance; Photoelectrochemical water splitting; Photophysical properties; Amorphous semiconductor; Band structure; CuSnO3; Heterojunction; Photoelectrochemical performance; Sol-gel method